Pengaruh Media Edukasi Berbasis Video terhadap Tingkat Pengetahuan Remaja Mengenai Kesehatan Reproduksi di Pondok Pesantren Al Kautsar Tangerang Tahun 2026 - Anes Patriakumala; Nita Tri Wahyuni; Herselowati; Anisa Nurul Khasanah (Jurnal Obstretika Scientia, 2026)
The urgency of unresolved adolescent reproductive health issues, including unwanted pregnancies (Fitriana, 2023). Limited access to accurate information leads many adolescents to acquire knowledge from unreliable sources, such as peer conversations or unverified digital content. As a result, adolescents are more vulnerable to risky behaviors such as premarital sex, sexually transmitted infections (STI), and unplanned pregnancies (BKKBN, 2022). Based on a preliminary study conducted over approximately one week, it was found that 7 out of 10 students at Al Kautsar Islamic Boarding School had insufficient knowledge about reproductive health. This research is an experimental study with a pre-experimental design. The research design used a one-group pretest-posttest design. The sample in this study used a total sampling technique, taking all members of the population without considering strata or levels within the population. The sample size for this study was 78 students at Al Kautsar Islamic Boarding School, Tangerang. The average knowledge before and after was 70.39 and 86.73, respectively. The increase in knowledge before and after was 16.34. The Wilcoxon test showed a p-value of 0.000 < 0.05. There is a difference in the impact of video-based educational media on adolescents' knowledge levels regarding reproductive health at the Al Kautsar Islamic Boarding School in Tangerang.